2020
DOI: 10.21203/rs.3.rs-70730/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electrical Conductive Fluidized Zones and Their Influence on the Earthquake Nucleation, Growth, and Arrest Processes of the 2016 Kumamoto Earthquake Sequence, Kyushu Island, Japan

Abstract: Crustal earthquake ruptures tend to nucleate near fluidized zones. However, it is relatively unknown whether fluidized zones can further promote or arrest these ruptures. We image the electrical resistivity structure around the focal area of the 2016 Kumamoto earthquake sequence by using 200 sites broad-band magnetotelluric data, and discuss its quantitative relationship to earthquake nucleation, growth, and arrest processes. The result shows that the earthquake hypocenters are all located within 10 km from lo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The fault‐valve hypothesis of Sibson (1992) suggests that overpressured fluid reduces the frictional fault strength, inducing the earthquake and promoting upward fluid flow from deep fluid‐rich reservoirs to the shallower crust, but the fluid pressure drop after the fault rupture subsequently reverses and rises once again. Recently, it is suggested that the overpressured fluids not only contribute to the initiation of earthquakes but also contribute to the final magnitude of earthquakes (Aizawa et al., 2021). Based on the fault‐valve hypothesis, it is likely that electrical conductors under the UF, AF, and TOFZ contain suprahydrostatic fluids, which can induce intraplate earthquakes at the faults in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fault‐valve hypothesis of Sibson (1992) suggests that overpressured fluid reduces the frictional fault strength, inducing the earthquake and promoting upward fluid flow from deep fluid‐rich reservoirs to the shallower crust, but the fluid pressure drop after the fault rupture subsequently reverses and rises once again. Recently, it is suggested that the overpressured fluids not only contribute to the initiation of earthquakes but also contribute to the final magnitude of earthquakes (Aizawa et al., 2021). Based on the fault‐valve hypothesis, it is likely that electrical conductors under the UF, AF, and TOFZ contain suprahydrostatic fluids, which can induce intraplate earthquakes at the faults in the future.…”
Section: Discussionmentioning
confidence: 99%
“…(2020) found mid‐to‐lower‐crustal conductors associated with seismogenic structures of some strong earthquakes. Moreover, in Japan, several electromagnetic induction surveys have identified electrical conductors close to seismically active regions and have discussed the influences of fluids on earthquakes (e.g., Aizawa et al., 2021; Ichihara et al., 2011; Ogawa & Honkura, 2004; Ogawa et al., 2001; Uyeshima et al., 2005; Yoshimura et al., 2008).…”
Section: Introductionmentioning
confidence: 99%